Respostas

2014-02-02T21:26:51-02:00
A)  -8 + (-81):(-27) =
     -8 + 3 = -5
b) (-121):(-11) + (+8).(+9)=
             11       +    72       = 83
c) (-3).(-5+7) =
     -3  . +2     =  -6
d) (5-1):(-6+3):(-2-8)=
       4   :   -3    : -10  =  2/15
1 3 1
Muito bom,Luiz . Parabéns!
Obrigado. Estamos todos aprendendo !!!
Verdade.
2014-02-02T22:34:49-02:00
*  -8 + (-81):(-27) = 
     -8 + 3 = -5
* (-121):(-11) + (+8).(+9)=
             11       +    72       = 83
* (-3).(-5+7) =
     -3  . +2     =  -6
* (5-1):(-6+3):(-2-8)=
       4   :   -3    : -10  =  2/15
Espero q ajude :))